Acute kidney injury in polymorbid patients - Marina V. Lebedeva; Elena S. Kamyshova; Marina V. Taranova; Vladimir D. Beketov; Elena Yu. Andreeva (LLC "MEDIAFORMAT", 2024)
The presented clinical observation shows the role of a multidisciplinary team of doctors in the treatment of acute kidney injury (AKI) in a patient suffering from bronchial asthma and metabolic syndrome (morbid obesity, arterial hypertension, type 2 diabetes mellitus). The importance of correcting metabolic disorders (diet, self-monitoring of glycemia, urate- and glucose-lowering therapy) has been demonstrated both as part of the complex therapy of AKI and for the prevention/slowing of further kidney damage.